Populasi Elaeidobius kamerunicus Faust (Coleoptera: Curculionidae) pada beberapa umur tanaman kelapa sawit - Rahardjo, Bambang Tri; Rizali, Akhmad; Utami, Ika Putri; Karindah, Sri; Puspitarini, Retno Dyah; Sahari, Bandung (Perhimpunan Entomologi Indonesia, 2018)
Elaeidobius kamerunicus Faust is an oil palm pollinator insect that lives on the male inflorescence and visits female inflorescence to pollinate due to attracted by its volatile compound. The number of fruit sets of oil palm relates to the population of E. kamerunicus on a plantation. The objective of this study was to investigate the effect of age of oil palm on the population of E. kamerunicus. Field research was conducted in oil palm plantations that located in Pangkalan Lada, Kotawaringin Barat District, in Central Kalimantan. The research method was by measurement of E. camerunicus population on male inflorescences and set up the sticky trap on female inflorescences. Plot with size 7000 m2 (100 trees) was selected on several ages of oil palm i.e. 6, 10 and 16 years. Each plot, the number of male and female inflorescences was counted and some inflorescences were chosen for measurement of E. camerunicus population that was conducted monthly for three months of observation. The results showed that the age of the oil palm affected the population of E. kamerunicus in male inflorescences but not in female inflorescences. The older age of oil palm, the population of E. kamerunicus in male flowers was increasing. The sex ratio of E. kamerunicus found in male and female inflorescences of oil palms tend to female bias. Based on the comparison of E. kamerunicus population between male and female inflorescences on each plot, it was found that visitation value of E. kamerunicus was highest in the young oil palm. In conclusion, increasing age of oil palm trees affected on increasing of E. kamerunicus population in male inflorescences, but visitation value on female inflorescences prone to decline.